Recharge sources and genesis of underground brines in the Mahai Basin, Qaidam Basin, China: insights from hydrochemistry and multi-isotope tracers - Ruibo Liu; Xiwei Qin; Wenquan Lu; Haiyan Shi; Zhen Shi; Chenglin Liu; Ying Ma; Xiangjun Li; Sha Yang; Ziwen Jiang; Genhou Wang; Ming Ma; et al. (Carbonates and Evaporites, 2026)

Precursor rigidity engineering enables synergistic regulation of closed pores and graphitic domains for balancing energy and power densities in hard carbon anodes - Qiaofeng Huang; Yiwen Sun; Haoliang Lin; Yuhai Wang; Yifan Sha; Weizhen Fan; Litao Shi; Yu Ying; Xianjian Duan; Chunlei Wu; Guang Shi (Chemical Engineering Journal, 2026)

Poly(phenol-imidazole) nanosheets engineered multifunctional hydrogel for promotion of infected diabetic wound healing - Jia Xin Yu; Lu Yao Li; Yu Fan; Piao Zheng; Sha Yang; Qi Fang Liu; Cai Juan Huang; Ya Lin Cao; Yang You (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Microplastics-induced effects on membrane fouling and effluent quality in MBRs for landfill leachate treatment under long-term operation - Shijie Bian; Jingwei Yan; Timing Jiang; Huying Li; Rui Cai; Wen Li; Jingjing Shi; Fan Yang; Sha Liang; Huabo Duan; Wenbo Yu; Shushan Yuan; et al. (Waste Management, 2026)

Gastrointestinal digestive fate of squid cartilage collagen peptides: degradation characteristics and the key role of Gly-Pro skeleton structure - Xuanli Sha; Yueting Guo; Yan Fan; Tingting Yang; Liping Zheng; Shiqi Li; Hu Hou (Food Chemistry, 2026)

Engineering exposed crystal planes of ZIF-8 to tune the surface coordination environment for stable zinc metal anodes - Yao Dai; Wenhao Li; Huilin Fan; Runguo Zheng; Zhiyuan Wang; Sha Liu; Hongyu Sun; Yanguo Liu (Chemical Engineering Journal, 2026)

Identifying RNA ac4C Modification Sites via Pseudo-Nucleotide Fingerprint Encoding and Multi-Scale Feature Integration - Yiming Wang; Fan Mo; Yun Sha; Zhenguo Wen; Chun Fang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Calcium and TRPML-Mediated Autophagy: Implications in Cancer, Cardiovascular Diseases, and Cardio-Oncology - Joseph Adu-Amankwaah; Vincent Kawuribi; Manuella Quaye; Ling Sha; Siwen Fan; Prakriti Kaur; Vishal Sharma; Osinachi Uchechi Okpoko; Zeyuan Yin (Cardiovascular Toxicology, 2026)

Co-Pyrolysis of Titanium Gypsum and Cow Dung to Prepare Modified Biochar for Phosphorus Adsorption in Water - Dongyi Li; He Li; Zhigang Liu; Kexin Xu; Pengfei Wu; Aiguo Sha; Fan Li (Water, Air, & Soil Pollution, 2026)

Source Apportionment of Nitrate Pollution in the Ling River Basin Based on Nitrogen and Oxygen Isotopes and Hydrochemical Analysis - Lili Fan; Haiming Lu; Liangang Chen; Haifei Sha; Kai Wang; Qiu Jin; Shucheng Wu; Qinxue Xu; Junhong Chen; Qixiao Zhang; Minghui Liu; Lang Tan (Bulletin of Environmental Contamination and Toxicology, 2026)

Advanced strategies for selective lithium extraction from spent lithium-ion battery cathodes - Ying Zheng; Ziwen Dai; Fan Yang; Zhaoyang Li; Guang Hu; Sha Liang; Wenbo Yu; Shushan Yuan; Huabo Duan; Liang Huang; Jingping Hu; Huijie Hou; et al. (Resources, Conservation and Recycling, 2026)

Maternal mRNA clearance is associated with the prevention of precocious transcription and genome instability in mouse early embryos - Qian-Qian Sha; Yun-Wen Wu; Meng-Yan Jia; Yu Jiang; Xing-Xing Dai; Long-Wen Zhao; Heng-Yu Fan (Science Bulletin, 2026)

Intranasal biomimetic vesicle platform reprograms the glioblastoma microenvironment for enhanced immunotherapy - Shuo Li; Chao Qin; Fan-Yu Qian; Jin-Hao Wang; Xiang-Gui Wu; Wen-Qing Li; Tai-Yu Liu; Zhao-Jie Chen; Bei-Yuan Zhang; Qi-Yue Liu; Li-Sha Liu; Li-Fang Yin (Chemical Engineering Journal, 2026)

One-step rapid synthesis Ti-O-rich Ti3C2 MXene via NH4HF2 hydrothermal etching for high charge storage - Xuefeng Sha; Xianyin Song; Qiwei Shangguan; Yawei Lv; Fan Zeng; Xingang Zhang; Xueli Wu; Minghao Yu; Changzhong Jiang (Chemical Engineering Journal, 2026)

Material source and genesis analysis of lithium-rich claystone in Balun Mahai Salt Lake, Qaidam Basin - Fan Zhang; Xiwei Qin; Yuliang Ma; Sha Yang; Tong Pan; Jianzhou Chen; Chenglin Liu; Chengwang Ding; Ziwen Jiang; Dong Zhang; Qingkuan Li; Genhou Wang; et al. (Journal of Geochemical Exploration, 2026)

Dietary soybean isoflavones modulate reproductive hormones and immunity by altering rumen microbiota in ewes - Mengqi Lou; Xiongxiong Li; Shengguo Zhao; Jinlong Xu; Qingshan Fan; Yuzhu Sha; Jie Bai; Ting Jiao (Animal Feed Science and Technology, 2026)

Linking ENSO diversity to runoff predictability in China using nonhomogeneous hidden Markov model - Jian Sun; Lei Yan; Jinxia Sha; Dan Xu; Fan Lu; Qinghua Luan; Yuan Liu; Boyuan Lu; Cong Jiang; Lihua Xiong (Journal of Hydrology, 2026)

Water-sediment regulation drives multi-taxon biodiversity and ecological network dynamics in the Yellow River Estuary - Cheng-Rui Yan; Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2025)

Microbiome and pathogen identification, and associated antimicrobial resistance genes and virulence factors in seafood revealed by 16S rRNA amplicon and metagenomic sequencing - Xin Gao; Peiyong Ning; Sha Luo; Yuan Wang; Wen Li; Xiaoqing Fan; Xiaoyan Li (International Journal of Food Microbiology, 2025)

CDK5-Induced HCN2 Channel Dysfunction in the Prelimbic Cortex Drives Allodynia and Anxiety-Like Behaviors in Neuropathic Pain - Lu Chen; Shuai Cao; Yun-Ze Liu; Qi-Fan Yang; Jin-Yu Yang; Dan-Yang Zhang; Guo-Guang Xie; Xiang-Sha Yin; Ying Zhang; Yun Wang (Neuroscience Bulletin, 2025)

Machine Learning Improves Mesoscale Offshore Wind Resource Assessment over the Yellow Sea - Haixing Gong; Kan Yi; Dinghua Yang; Wenyu Huang; Chenqing Fan; Ran Hao; Lina Sha; Mengke Deng; Hao Zhang (Journal of Meteorological Research, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Synthesis of lithium-ion sieves based on electrolytic manganese anode slime: Characterization and its lithium adsorption performance - Jun Luo; Jiancheng Shu; Hongyuan Zhao; Jing Wang; Shaoqin Chen; Huimin Yang; Fan Lin; Sha Zhang; Mengjun Chen; Yong Yang (Chemical Engineering Journal, 2025)

Novel alkali-resistant nitrogen and phosphorus removal strain I4: Performance evaluation and molecular mechanism - Xiaoxuan Fan; Jiayi Zhou; Qionghua Chen; Yuwei Feng; Ruirui Han; Guangfeng Chen; Sha Yue; Yonghao Ma; Hu Shu (Bioresource Technology, 2025)

Microphysical characteristics of precipitation during a cold-season elevated thunderstorm event in Henan, China - Jianfang Ding; Bo Cheng; Hui Xiao; Ting Bai; Can Song; Xiuzhu Sha; Lei Liu; Fan Zhang; Yanhua Liu (Atmospheric Research, 2025)

Dynamics of vegetation response patterns to drought and its driving factors across China's Loess Plateau - Jingxuan Su; Liangxin Fan; Zhanliang Yuan; Sha Xue (Journal of Environmental Management, 2025)

DCNet: Full waveform inversion with difference convolution - Li-Sha Fu; Chang-Yang Hu; Leting Tan; Huawei Liao; Qiang Zhang; Fan Min (Journal of Applied Geophysics, 2025)

Microbiome catalog and dynamics of the Chinese liquor fermentation process - Xue Zhu; Liangqiang Chen; Pengshuo Yang; Sha Luo; Mengjing Teng; Wenjie Zhu; Yuxue Li; Dan Zhao; Nan Wang; Xiaoke Chen; Mingyue Cheng; Huabin Tu; et al. (Bioresource Technology, 2025)

NPK-N application limits grain cadmium concentration of wheat via promoting Cd export during grain filling - Yiran Cheng; Yuanjiang He; Jia Chen; Weiping Li; Wenhui Xiang; Xing Chen; Dan Long; Jian Zeng; Yang Liu; Dongwei Wang; Dandan Wu; Lina Sha; et al. (Plant and Soil, 2025)

Unlocking Stress Responses: Exploring PseWRKY51 and PseWRKY60 in Pseudoroegneria libanotica Through Comprehensive Analysis of the WRKY Gene Family Under Abiotic Challenges - Xunzhe Yang; Xia Wang; Xiang Li; Chen Chen; Dandan Wu; Yiran Cheng; Yi Wang; Lina Sha; Houyang Kang; Xing Fan; Yinglong Chen; Yonghong Zhou; et al. (Journal of Plant Growth Regulation, 2025)

Identification and Characterization of LBD Gene Family in Pseudoroegneria libanotica Reveals Functions of PseLBD1 and PseLBD12 in Response to Abiotic Stress - Xunzhe Yang; Xiang Li; Xia Wang; Chen Chen; Dandan Wu; Yiran Cheng; Yi Wang; Lina Sha; Houyang Kang; Songqing Liu; Xing Fan; Yinglong Chen; et al. (Biochemical Genetics, 2025)

Study on novel alkali-activated cementitious grout for scour control of offshore foundation - Fei Sha; Yulong Dong; Shijiu Gu; Xiaochen Fan; Wenwen Xiao (Geomechanics for Energy and the Environment, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

Response of vegetation evapotranspiration to landscape pattern changes in an arid region: A case study of the Loess Plateau, China - Jin Guo; Liangxin Fan; Pengfei Feng; Xialing Sun; Sha Xue (CATENA, 2025)

Enhanced phosphorus bioavailability of biochar derived from sewage sludge co-pyrolyzed with K, Ca-rich biomass ash - Xiao Guo; Sha Liang; Zhengkang Zou; Xiaoxiao Xu; Fan Yang; Junda Quan; Xingwu Li; Huabo Duan; Wenbo Yu; Jiakuan Yang (Water Research, 2025)

Devosia alba sp. nov., a potential nitrite-reducing bacterium isolated from a mudflat - Sha-sha Qiu; Hong-zhe Hu; Yi-fan Zhuo; Yue Su; Yu-si Yang; Tao Wang; Qi-yun Zheng; Xin-yi Huang; Ailina Yilibao; Can Chen (Current Microbiology, 2025)

Synthesis of value-added uridine 5'-diphosphate-glucose from sucrose applying an engineered sucrose synthase counteracts the activity-stability trade-off - Liting Zhao; Zhongbao Ma; Linpei Zhang; Yu Shen; Lei Chen; Youran Li; Sha Xu; Guiyang Shi; Daming Fan; Zhongyang Ding (Food Chemistry, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

A framework of ecological security patterns in arid and semi-arid regions considering differences socioeconomic scenarios in ecological risk: Case of Loess Plateau, China - Jin Guo; Pengfei Feng; Han Xue; Sha Xue; Liangxin Fan (Journal of Environmental Management, 2025)

Does land use change decline the regional ecosystem health maintenance? Case study in subtropical coastal region, Fuzhou, China - Zhipeng Fan; Xiaomei Li; Chaowu Yang; Hao Zhang; Xulin Guo; Shuhui Lai; Jinming Sha (Journal of Environmental Management, 2025)

A droplet memristor with ionic liquid-electrolyte meniscus - Wei Liu; Jianyu Shang; Fei Zheng; Qinyang Fan; Xiaoxuan Yuan; Yunfei Chen; Jingjie Sha (Chemical Engineering Journal, 2025)

Comprehensive evaluation of bioavailable phosphorus in biochar synthesized by co-pyrolysis of sewage sludge and straw ash - Xiaoxiao Xu; Zhengkang Zou; Xiao Guo; Sha Liang; Fan Yang; Shuai Chen; Wenbo Yu; Huabo Duan; Shushan Yuan; Jiakuan Yang (Science of The Total Environment, 2024)

Efficient phosphorus recovery from simulated phosphoric acid wastewater using a tailored dual-module flow electrode capacitive deionization (FCDI) strategy - Fan Yang; Shuai Chen; Sha Liang; Mingxuan Wen; Junda Quan; Xiong Shi; Shushan Yuan; Huabo Duan; Wenbo Yu; Liang Huang; Jiakuan Yang (Resources, Conservation and Recycling, 2024)

Efficient removal of radioactive Th(IV) and U(VI) from rare earth leaching solution using HDES - Lei-Tao Sha; Qiang Wu; Yi-Fan Zhang; Wei-Jia Wang; Fei Wu; Qing-Gang Huang; Ze-Yi Yan (Chemical Engineering Journal, 2024)

Analysis of the temporal and spatial changes of ecological environment quality using the optimization remote sensing ecological index in the middle Yellow River Basin, China - Guanwen Li; Naichang Zhang; Yongxiang Cao; Zhaohui Xia; Chenfang Bao; Liangxin Fan; Sha Xue (Earth Science Informatics, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Spatially separated redox active sites over Re-Ni@Ni(OH)2 core-shell structure for enhancing furfural oxidation coupled with hydrogen evolution - Qing-Qing Pang; Xi-Zheng Fan; Sha-Sha Yi; Xin Du; Zhong-Yi Liu; Xin-Zheng Yue (Chemical Engineering Journal, 2024)

Constructing multi-dimensional alternating layer nested structure for enhancing electromagnetic shielding, thermal management and strain sensing - Dingwen Yin; Jinbao Li; Simin Wang; Huijuan Xiu; Gengmei Liu; Shaoyan Huang; Sha Fan; Mengxia Shen; Yanfei Pan (Chemical Engineering Journal, 2024)

Development of wheat-tetraploid Thinopyrum elongatum 4EL small fragment translocation lines with stripe rust resistance gene Yr4EL - Biran Gong; Jing Gao; Yangqiu Xie; Hao Zhang; Wei Zhu; Lili Xu; Yiran Cheng; Yi Wang; Jian Zeng; Xing Fan; Lina Sha; Haiqin Zhang; et al. (Theoretical and Applied Genetics, 2024)

Impact of rice variety, cooking equipment and pretreatment method on the quality of lightly milled rice - Shishan Zhao; Jianbin Shi; Sha Cai; Tian Xiong; Fang Cai; Shaobin Li; Xueling Chen; Chuanhui Fan; Xin Mei; Yong Sui (Food Chemistry, 2024)

Temporal accumulation and lag effects of precipitation on carbon fluxes in terrestrial ecosystems across semi-arid regions in China - Haixing Gong; Guoyin Wang; Chenqing Fan; Xianwang Zhuo; Lina Sha; Zexing Kuang; Jianrong Bi; Tiantao Cheng (Agricultural and Forest Meteorology, 2024)

Fabrication of high mechanical strength and high porosity PVDF isoporous membranes based on inverse opal photonic crystals - Sha Fan; Yu Wang; Xinyi Hong; Gaofeng Liu; Chengcai Li; Hailin Zhu; Bin Yu; Guojin Liu (Journal of Water Process Engineering, 2024)

Wave, flow, and suspended sediment dynamics under strong winds on a tidal beach - Lingpeng Meng; Junbiao Tu; Xiaodong Wu; Sha Lou; Jun Cheng; Sergey Chalov; Xiangju Han; Daidu Fan (Estuarine, Coastal and Shelf Science, 2024)

High efficiency triethylamine gas sensor based on SmVO4 nano octahedron granules - Cheng Yu Xu; Shu Yi Ma; Tian Yuan Dong; Ji Ming Liu; Jin Sha Wei; Hong Tao Jiang; Ping Ni; Ge Ge Fan; Jia Yun Guo (Journal of Environmental Chemical Engineering, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Effects of tire–road wear particles on the adsorption of tetracycline by aquatic sediments - Xiulei Fan; Binwen Cao; Shenpeng Wang; Huixian Li; Mingxian Zhu; Haidi Sha; Yangyang Yang (Environmental Science and Pollution Research, 2024)

Water-sediment regulation affects community structures of macrobenthic mollusks in the Yellow River estuary and adjacent waters - Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2024)

Immunostimulant citrus fruit-derived extracellular vesicle nanodrugs for malignant glioma immunochemotherapy - Jinheng Li; Xuejiao Wang; Haoyan Guo; Houwang Zhou; Suinan Sha; Yulu Yang; Jianping Chen; Xiangrong Hao; Jiahao Pan; Ying Wang; Jun-Bing Fan (Chemical Engineering Journal, 2024)

Genome-wide identification of bHLH transcription factors and expression analysis under drought stress in Pseudoroegneria libanotica at germination - Xingguan Zhai; Xia Wang; Xunzhe Yang; Qingxiang Huang; Dandan Wu; Yi Wang; Houyang Kang; Lina Sha; Xing Fan; Yonghong Zhou; Haiqin Zhang (Physiology and Molecular Biology of Plants, 2024)

A flexible method for BDS-3 multi-frequency phase observable-specific biases estimation and its PPP analysis with different ambiguity resolution strategies - Kun Chen; Shirong Ye; Yongzhao Fan; Hao Luo; Zhimin Sha; Jianhui Liu (Advances in Space Research, 2024)

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

Carbon footprints, mitigation effects and economic performance of dairy farm systems in Inner Mongolia - Sha Wei; Stewart Ledgard; Junming Fan; Yanfeng Tian; Hongmin Dong (Agricultural Systems, 2024)

Microwave heating moment, thermal characteristics, and structural variations of different steel slag asphalt mixtures suffered from freeze-thaw damage - Fan Zhang; Aimin Sha; Yangsen Cao; Wentong Wang; Ruimeng Song (Cold Regions Science and Technology, 2024)

Development, identification, and utilization of wheat–tetraploid Thinopyrum elongatum 4EL translocation lines resistant to stripe rust - Biran Gong; Linfeng Chen; Hao Zhang; Wei Zhu; Lili Xu; Yiran Cheng; Yi Wang; Jian Zeng; Xing Fan; Lina Sha; Haiqin Zhang; Guoyue Chen; et al. (Theoretical and Applied Genetics, 2024)

JAZ1 gene regulates starch biosynthesis and changes physicochemical properties in wheat grains - Sha-Sha Yuan; Peng Fan; Dan-Dan Zhang; Hai-Tao Liu; Peng-Fei Wang; Tian-Cai Guo; Ge-Zi Li; Yong-Hua Wang; Guo-Zhang Kang (Food Bioscience, 2023)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Histological Assessment and Transcriptome Analysis Provide Insights into the Toxic Effects of Perfluorooctanoic Acid to Juvenile Half Smooth Tongue Sole Cynoglossus semilaevis - Min Zhan; Kunpeng Shi; Xue Zhang; Qingxin Fan; Qian Xu; Xinbao Liu; Zhujun Li; Hongning Liu; Yanting Xia; Zhenxia Sha (Journal of Ocean University of China, 2023)

Inflammatory reaction and immune response of half-smooth tongue sole (Cynoglossus semilaevis) after infection with Vibrio anguillarum - Wenwen Wang; Qian Xu; Shaoqing Zang; Xinbao Liu; Hongning Liu; Zhujun Li; Qingxin Fan; Suxu Tan; Kunpeng Shi; Yanting Xia; Zhenxia Sha (Fish & Shellfish Immunology, 2023)

Craniocervical Manual Lymphatic Drainage Increases the Efficiency of Atorvastatin-Based Treatment of Chronic Subdural Hematoma - Chuang Gao; Yingsheng Wei; Xinjie Zhang; Jinhao Huang; Meng Nie; Xuanhui Liu; Jiangyuan Yuan; Dong Wang; Ye Tian; Weiwei Jiang; Shuo An; Jian Sun; et al. (Translational Stroke Research, 2023)

Supervised Mineral Prospectivity Mapping via Class-Balanced Focal Loss Function on Imbalanced Geoscience Datasets - Zhiqiang Zhang; Yingjie Li; Gongwen Wang; Emmanuel John M. Carranza; Shuren Yang; Deming Sha; Junjie Fan; Xiang Zhang; Yulong Dong (Mathematical Geosciences, 2023)

Exploring the effect of Ulva prolifera decay on the immune tissue of Paralichthys olivaceus based on transcriptomics and histopathological analysis - Kunpeng Shi; Qingxin Fan; Min Zhan; Min Pang; Suxu Tan; Wenwen Wang; Muyuan Wang; Zhenxia Sha (Marine Pollution Bulletin, 2023)

Diterpenoids from Euphorbia lactea and their anti-HIV-1 activity - Ye Zhao; Chen Hua; Yi-ou Sha; Pei-Qian Wu; Qun-Fang Liu; Lu Lu; Bin Zhou; Shi-bo Jiang; Yao-Yue Fan; Jian-Min Yue (Phytochemistry, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Chromosome-specific painting in Thinopyrum species using bulked oligonucleotides - Chen Chen; Yangshuo Han; He Xiao; Bingcan Zou; Dandan Wu; Lina Sha; Cairong Yang; Songqing Liu; Yiran Cheng; Yi Wang; Houyang Kang; Xing Fan; et al. (Theoretical and Applied Genetics, 2023)

miR-671-5p Upregulation Attenuates Blood–Brain Barrier Disruption in the Ischemia Stroke Model Via the NF-кB/MMP-9 Signaling Pathway - Ling Deng; Jiyu Zhang; Sha Chen; Yu Wu; Xiaomei Fan; Tianrui Zuo; Qingwen Hu; Lu Jiang; Shaonan Yang; Zhi Dong (Molecular Neurobiology, 2023)

A sustainable strategy for recovery of phosphorus as vivianite from sewage sludge via alkali-activated pyrolysis, water leaching and crystallization - Liang Yang; Xiao Guo; Sha Liang; Fan Yang; Mingxuan Wen; Shushan Yuan; Keke Xiao; Wenbo Yu; Jingping Hu; Huijie Hou; Jiakuan Yang (Water Research, 2023)

Manganese and copper additions differently reduced cadmium uptake and accumulation in dwarf Polish wheat (Triticum polonicum L.) - Xing Chen; Shan Yang; Jian Ma; Yiwen Huang; Yi Wang; Jian Zeng; Jun Li; Siyu Li; Dan Long; Xue Xiao; Lina Sha; Dandan Wu; et al. (Journal of Hazardous Materials, 2023)

Desorption behavior of antibiotics by microplastics (tire wear particles) in simulated gastrointestinal fluids - Xiulei Fan; Shenwen Qian; Yiquan Bao; Haidi Sha; Yiming Liu; Binwen Cao (Environmental Pollution, 2023)

Co-pyrolysis technology for enhancing the functionality of sewage sludge biochar and immobilizing heavy metals - Zeyu Fan; Xian Zhou; Ziling Peng; Sha Wan; Zhuo Fan Gao; Shanshan Deng; Luling Tong; Wei Han; Xia Chen (Chemosphere, 2023)

MUSER and IPS telescopes for solar and space weather observations - Yihua Yan; Wei Wang; Linjie Chen; Fei Liu; Jin Fan; Zhijun Chen; Lihong Geng; Chengming Tan; Suli Ma; Sha Li; Cang Su; Jing Du; et al. (Advances in Space Research, 2023)

Design and synthesis of SO3H-functionalized acidic ionic liquids for catalytic conversion of wheat straw to ethyl levulinate - Chao Li; Jian Zhao; Huixin Tong; Xiaodong Fan; Xinjie Fang; Yuli Sha; Zhizhong Sun; Wenyi Chu (Fuel, 2023)

Tumor microenvironment activated nanoreactors for chemiluminescence imaging-guided simultaneous elimination of breast tumors and tumor-resident intracellular pathogens - Xinxin Li; Ting Wu; Zefan Zhang; Sha Liu; Hongmei Cui; Zhongxiong Fan; Baodui Wang; Jun Hai (Chemical Engineering Journal, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

FeCl3 and Fe2(SO4)3 differentially reduce Cd uptake and accumulation in Polish wheat (Triticum polonicum L.) seedlings by exporting Cd from roots and limiting Cd binding in the root cell walls - Qin Yao; Weiping Li; Ying Liu; Yiran Cheng; Xue Xiao; Dan Long; Jian Zeng; Dandan Wu; Lina Sha; Xing Fan; Houyang Kang; Haiqin Zhang; et al. (Environmental Pollution, 2023)

Fluid-structure interaction analysis of oblique ship-bridge collisions - Xudong Ye; Wei Fan; Yanyan Sha; Xugang Hua; Qinglin Wu; Yongli Ren (Engineering Structures, 2023)

In-situ growth of Ni(OH)2 nanoplates on highly oxidized graphene for all-solid-state flexible supercapacitors - Xueli Wu; Fan Zeng; Xianyin Song; Xuefeng Sha; Hongtao Zhou; Xingang Zhang; Zhi Liu; Minghao Yu; Changzhong Jiang (Chemical Engineering Journal, 2023)

An Integrated Framework for Data-Driven Mineral Prospectivity Mapping Using Bagging-Based Positive-Unlabeled Learning and Bayesian Cost-Sensitive Logistic Regression - Zhiqiang Zhang; Gongwen Wang; Emmanuel John M. Carranza; Junjie Fan; Xinxing Liu; Xiang Zhang; Yulong Dong; XiaoPeng Chang; Deming Sha (Natural Resources Research, 2022)

A two-year (2020–2021) observation of marine phycotoxins in phytoplankton in typical mariculture areas of East China Sea - Xiaoqing Tian; Chengqi Fan; Yunyu Tang; Haiyan Zhang; Wei Kang; Sha Chen; Chongbin Li; Ya’nan Lu (Journal of Oceanology and Limnology, 2022)

Fine mapping of the reduced height gene Rht22 in tetraploid wheat landrace Jianyangailanmai (Triticum turgidum L.) - Chao Wang; Yunjing Bao; Qin Yao; Dan Long; Xue Xiao; Xing Fan; Houyang Kang; Jian Zeng; Lina Sha; Haiqin Zhang; Dandan Wu; Yonghong Zhou; et al. (Theoretical and Applied Genetics, 2022)

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

Disassociated and concurrent structural and functional abnormalities in the drug-naïve first-episode early onset schizophrenia - Qiang Li; Sha Liu; Xiaohua Cao; Zexuan Li; Yun-shuang Fan; Yanfang Wang; Jiaojian Wang; Yong Xu (Brain Imaging and Behavior, 2022)
Schizophrenia which is an abnormally developmental disease has been widely reported to show abnormal brain structure and function. Enhanced functional integration is a predominant neural marker for brain mature. Abnormal development of structure and functional integration may be a biomarker for early diagnosis of schizophrenia. Fifty-five patients with early onset schizophrenia (EOS) and 79 healthy controls were enrolled in this study. Voxel-based morphometry (VBM) and functional connectivity density (FCD) were performed to explore gray matter volume (GMV) lesion, abnormal functional integration, and concurrent structural and functional abnormalities in the brain. Furthermore, the relationships between abnormalities structural and function and clinical characteristics were evaluated in EOS. Compared with healthy controls, EOS showed significantly decreased GMV in the bilateral OFC, frontal, temporal, occipital, parietal and limbic system. EOS also showed decreased FCD in precuneus and increased FCD in cerebellum. Moreover, we found concurrent changes of structure and function in left lateral orbitofrontal cortex (lOFC). Finally, correlation analyses did not find significant correlation between abnormal neural measurements and clinical characteristic in EOS. The results reveal disassociated and bound structural and functional abnormalities patterns in EOS suggesting structural and functional measurements play different roles in delineating the abnormal patterns of EOS. The concurrent structural and functional changes in lOFC may be a biomarker for early diagnosis of schizophrenia. Our findings will deepen our understanding of the pathophysiological mechanisms in EOS.

The SACT Template: A Human Brain Diffusion Tensor Template for School-age Children - Congying Chu; Haoran Guan; Sangma Xie; Yanpei Wang; Jie Luo; Gai Zhao; Zhiying Pan; Mingming Hu; Weiwei Men; Shuping Tan; Jia-Hong Gao; Shaozheng Qin; et al. (Neuroscience Bulletin, 2022)

Altered albedo dominates the radiative forcing changes in a subtropical forest following an extreme snow event - Palingamoorthy Gnanamoorthy; Qinghai Song; Junbin Zhao; Yiping Zhang; Yuntong Liu; Wenjun Zhou; Liqing Sha; Zexin Fan; Pramit Kumar Deb Burman (Global Change Biology, 2021)
Subtropical forests are important ecosystems globally due to their extensive role in carbon sequestration. Extreme climate events are known to introduce disturbances in the ecosystem that cause long‐term changes in carbon balance and radiation reflectance. However, how these ecosystem function changes contribute to global warming in terms of radiative forcing (RF), especially in the years following a disturbance, still needs to be investigated. We studied an extreme snow event that occurred in a subtropical evergreen broadleaved forest in south‐western China in 2015 and used 9 years (2011–2019) of net ecosystem CO 2 exchange (NEE) and surface albedo ( α ) data to investigate the effect of the event on the ecosystem RF changes. In the year of the disturbance, leaf area index (LAI) declined by 40% and α by 32%. The annual NEE was −718 ± 128 g C m −2 as a sink in the pre‐disturbance years (2011–2014), but after the event, the sink strength dropped significantly by 76% (2015). Both the vegetation, indicated by LAI, and α recovered to pre‐disturbance levels in the fourth post‐disturbance year (2018). However, the NEE recovery lagged and occurred a year later in 2019, suggesting a more severe and lasting impact on the ecosystem carbon balance. Overall, the extreme event caused a positive (warming effect) net RF which was predominantly caused by changes in α (90%–93%) rather than those in NEE. This result suggests that, compared to the climate effect caused by forest carbon sequestration changes, the climate effect of α alterations can be more sensitive to vegetation damage induced by natural disturbances. Moreover, this study demonstrates the important role of vegetation recovery in driving canopy reflectance and ecosystem carbon balance during the post‐disturbance period, which determines the ecosystem feedbacks to the climate change.

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Short-term effects of ambient temperature on preterm birth: a time-series analysis in Xuzhou, China - Peng Cheng; Lei Peng; Jingwen Hao; Sha Li; Chao Zhang; Lianjie Dou; Weinan Fu; Fan Yang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Enzymatic hydroxylation of L-pipecolic acid by L-proline cis-4-hydroxylases and isomers separation - Fan Lu; Jiao Chen; Hai Ye; Hongli Wu; Feng Sha; Fujun Huang; Fei Cao; Ping Wei (Biotechnology Letters, 2020)

Differential Responses of Two Wheat Varieties Differing in Salt Tolerance to the Combined Stress of Mn and Salinity - Huajin Sheng; Jian Zeng; Yang Liu; Xiaolu Wang; Yi Wang; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou (Journal of Plant Growth Regulation, 2020)

Characterization of an Anti-CD5 Directed CAR T-Cell against T-Cell Malignancies - Masayuki Wada; Hongyu Zhang; Liu Fang; Jia Feng; Charlotte Olivia Tse; Wenli Zhang; Qi Chen; Sha Sha; Yuanzhen Cao; Kevin H. Chen; Kevin G. Pinz; Xi Chen; et al. (Stem Cell Reviews and Reports, 2020)

Visualizing DC morphology and T cell motility to characterize DC-T cell encounters in mouse lymph nodes under mTOR inhibition - Qiaoya Lin; Zheng Liu; Meijie Luo; Hao Zheng; Sha Qiao; Chenlu Han; Deqiang Deng; Zhan Fan; Yafang Lu; Zhihong Zhang; Qingming Luo (Science China Life Sciences, 2019)

Leaf Senescence can be Induced by Inhibition of Root Respiration - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zhu-yu Gu; Fan-jiang Zeng (Journal of Plant Growth Regulation, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Protective effect of different forms of nitrogen application on cadmium-induced toxicity in wheat seedlings - Lulu Yu; Xinxia Wang; Xiaoyuan Li; Yi Wang; Houyang Kang; Guangdeng Chen; Xing Fan; Lina Sha; Yonghong Zhou; Jian Zeng (Environmental Science and Pollution Research, 2019)

Expression of TpNRAMP5, a metal transporter from Polish wheat (Triticum polonicum L.), enhances the accumulation of Cd, Co and Mn in transgenic Arabidopsis plants - Fan Peng; Chao Wang; Jianshu Zhu; Jian Zeng; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou; Yi Wang (Planta, 2018)

Activated Biochar Prepared by Pomelo Peel Using H3PO4 for the Adsorption of Hexavalent Chromium: Performance and Mechanism - Yunhai Wu; Ligen Cha; Yiang Fan; Peng Fang; Zhu Ming; Haitao Sha (Water, Air, & Soil Pollution, 2017)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

Molecular cytogenetic characterization of a new wheat-rye 1BL•1RS translocation line expressing superior stripe rust resistance and enhanced grain yield - Weiliang Qi; Yao Tang; Wei Zhu; Daiyan Li; Chengdou Diao; Lili Xu; Jian Zeng; Yi Wang; Xing Fan; Lina Sha; Haiqin Zhang; Youliang Zheng; et al. (Planta, 2016)

Determining critical support discharge of a riverhead and river network analysis: Case studies of Lhasa River and Nyangqu River - Yukun Sha; Weipeng Li; Jihui Fan; Genwei Cheng (Chinese Geographical Science, 2016)

Adenylate kinase: a novel antigen for immunodiagnosis and subunit vaccine against tuberculosis - Yangjiong Xiao; Wei Sha; Zhaofeng Tian; Yingying Chen; Ping Ji; Qin Sun; Huiyu Wang; Shujun Wang; Yong Fang; Han-Li Wen; Hui-min Zhao; Jie Lu; et al. (Journal of Molecular Medicine, 2016)

Different causes of photosynthetic decline and water status in different stages of girdling in Alhagi sparsifolia Shap. (Fabaceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Fan-jiang Zeng (Brazilian Journal of Botany, 2016)

Molecular cloning of HMW glutenin subunits from Roegneria kamoji (Poaceae: Triticeae) - Ying-Xia Lei; Kuai Yu; Yi Wang; Xing Fan; Hou-Yang Kang; Li-Na Sha; Yong-Hong Zhou; Hai-Qin Zhang (Biologia, 2016)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

Effect of exogenous salicylic acid on manganese toxicity, mineral nutrients translocation and antioxidative system in polish wheat (Triticum polonicum L.) - Huajin Sheng; Jian Zeng; Fei Yan; Xiaolu Wang; Yi Wang; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou (Acta Physiologiae Plantarum, 2015)

Centromeric position and genomic allocation of a repetitive sequence isolated from chromosome 18D of hexaploid oat, Avena sativa L. - Xiaomei Luo; Nicholas A. Tinker; Haiqin Zhang; Charlene P. Wight; Houyang Kang; Xing Fan; Yi Wang; Lina Sha; Yonghong Zhou (Genetic Resources and Crop Evolution, 2015)

The altitudinal belts of subalpine virgin forest on Mt. Gongga simulated by a succession model - Gen-wei Cheng; Jian Sun; Yu-kun Sha; Ji-hui Fan (Journal of Mountain Science, 2014)

Spatiotemporal Change of Blue Water and Green Water Resources in the Headwater of Yellow River Basin, China - Weibin Zhang; Xiaochun Zha; Jiaxing Li; Wei Liang; Yugai Ma; Dongmei Fan; Sha Li (Water Resources Management, 2014)

Photosystem II activity of typical desert plant Alhagi sparsifolia Sharp.: response to exposure to natural light after being kept in shade - Lei Li; Xiang-yi Li; Xin-wen Xu; Li-sha Lin; Fan-jiang Zeng; Feng-li Chen (Trees, 2014)

Effects of high temperature on the chlorophyll a fluorescence of Alhagi sparsifolia at the southern Taklamakan Desert - Lei Li; Xiang-Yi Li; Xin-Wen Xu; Li-Sha Lin; Fan-Jiang Zeng (Acta Physiologiae Plantarum, 2014)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Production and cytogenetics of trigeneric hybrid involving Triticum, Psathyrostachys and Secale - Houyang Kang; Meiyu Zhong; Quan Xie; Haiqin Zhang; Xing Fan; Lina Sha; Lili Xu; Yonghong Zhou (Genetic Resources and Crop Evolution, 2012)

Study on regional production and economy of cobia Rachycentron canadum commercial cage culture - Cheng-Ting Huang; Sha Miao; Fan-Hua Nan; Shi-Mu Jung (Aquaculture International, 2011)

Molecular cloning, characterization and expression of cDNA encoding translationally controlled tumor protein (TCTP) from Jatropha curcas L - Xiaobo Qin; Fan Gao; Jinping Zhang; Jihai Gao; Sha Lin; Yong Wang; Luding Jiang; Yi Liao; Lina Wang; Yongjiong Jia; Lin Tang; Ying Xu; et al. (Molecular Biology Reports, 2011)

Development and characterization of wheat-Psathyrostachys huashanica partial amphiploids for resistance to stripe rust - Yi Wang; Quan Xie; Kangyu Yu; Vaino Poysa; Lijuan Lin; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou (Biotechnology Letters, 2011)

Establishment and characterization of a new cell line from the kidney of spotted halibut Verasper variegates - Xianli Wang; Songlin Chen; Zhenxia Sha; Tingjun Fan; Na Wang (Journal of Ocean University of China, 2010)

Association of the DRD2 and DRD3 polymorphisms with response to pramipexole in Parkinson’s disease patients - Ying-Zi Liu; Bei-Sha Tang; Xin-Xiang Yan; Jie Liu; Dong-Sheng Ouyang; Li-Nuo Nie; Lan Fan; Zhi Li; Wei Ji; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Inhibition on Hepatitis B virus in vitro of recombinant MAP30 from bitter melon - Jian Ming Fan; Qiao Zhang; Jun Xu; Sha Zhu; Tao Ke; De Fu Gao; Yu Bao Xu (Molecular Biology Reports, 2009)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)